Ontology-based context-sensitive software security knowledge management modeling - Mamdouh Alenezi (Institute of Advanced Engineering and Science, 2020)
The disconcerting increase in the number of security attacks on software calls for an imminent need for including secure development practices within the software development life cycle. The software security management system has received considerable attention lately and various efforts have been made in this direction. However, security is usually only considered in the early stages of the development of software. Thus, this leads to stating other vulnerabilities from a security perspective. Moreover, despite the abundance of security knowledge available online and in books, the systems that are being developed are seldom sufficiently secure. In this paper, we have highlighted the need for including application context sensitive modeling within a case-based software security management system. Furthermore, we have taken the context-driven and ontology-based frameworks and prioritized their attributes according to their weights which were achieved by using the Fuzzy AHP methodology.